Analysis of Total Quality Management (TQM), Performance Measurement System, Reward System and Organizational Commnitment to Managerial Performance on Dealer Bonanza Motor Lamongan) - Santika, Eva; Muhtarom, Abid; Fitrotun Najiah, Evi; Ruswaji, Ruswaji; Nurkholidah, Lilik; Nur Azizah, Luluk; Masruroh Isnawati, Uzlifatul (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2020)
Total Quality Management is a system that can be developed into a business approach to maximize the competitiveness of the organization through continual improvement of its products, services, manpower, processes and environment. In addition to the implementation of TQM, the company also implements other management accounting systems such as performance measuring systems and reward systems. The company also implements organizational commitments to increase the competitiveness of an organization. The purpose of this research is to know the influence of Total Quality Management, performance measurement system, appreciation system and organizational commitment to managerial performance at the Dealer BONANZA MOTOR Lamongan. The method used in this study was a saturated sample or a full sample of 70 respondents. The results of this study can be concluded that partial, TQM, Performance measurement systems and awards have no significant effect on managerial performance. Meanwhile, the organizational commitment has a partial effect on managerial performance. And simultaneously, TQM, performance measurement systems, reward systems and organizational commitments affect managerial performance. And the organizational commitment variables show the most dominant against managerial performance.